Silviculture Options for Use in Ranges Designated for the Conservation of Northern Caribou in British Columbia - McNay, Robert Scott (Canadian Institute for Studies in Publishing Press, 2011)
This review and synthesis of silviculture strategies was conducted to clarify options for managing forest stands in areas designated for conservation of habitat for the northern ecotype of woodland caribou in British Columbia. Information about the ecology, distribution, population status, and legal management measures for herds of northern caribou provided the background for assessing risk to forestry operations. A review of current scientific research and operational trials was used to reveal potential impacts of forestry on caribou life requisites. Specific attention was paid to the implications of the recent mountain pine beetle infestation. General guidelines (desired conditions) are provided for operating in areas designated for the conservation of caribou.